2012
DOI: 10.1503/jpn.110033
|View full text |Cite
|
Sign up to set email alerts
|

Event-related potentials and changes of brain rhythm oscillations during working memory activation in patients with first-episode psychosis

Abstract: Background: Earlier contributions have documented significant changes in sensory, attention-related endogenous event-related potential (ERP) components and theta band oscillatory responses during working memory activation in patients with schizophrenia. In patients with first-episode psychosis, such studies are still scarce and mostly focused on auditory sensory processing. The present study aimed to explore whether subtle deficits of cortical activation are present in these patients before the decline of work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 52 publications
(61 reference statements)
2
14
0
Order By: Relevance
“…An increase of gamma band activity was previously reported as being the consequence of a thalamocortical dysrhythmia that generates a cortical continuous theta coherent activity disinhibiting neighboring regions, hence giving rise to an ectopic gamma band activation referred to as the edge effect (Llinas et al 1999;Steriade 2006). Noteworthy that we previously demonstrated the presence of continuous theta activation in FEP patients (Missonnier et al 2012). The presence of an edge effect could contribute to the positive symptoms observed in patients, such as verbal hallucinations in the form of voices (Singer 1999;Llinas et al 2005).…”
Section: Discussionsupporting
confidence: 49%
“…An increase of gamma band activity was previously reported as being the consequence of a thalamocortical dysrhythmia that generates a cortical continuous theta coherent activity disinhibiting neighboring regions, hence giving rise to an ectopic gamma band activation referred to as the edge effect (Llinas et al 1999;Steriade 2006). Noteworthy that we previously demonstrated the presence of continuous theta activation in FEP patients (Missonnier et al 2012). The presence of an edge effect could contribute to the positive symptoms observed in patients, such as verbal hallucinations in the form of voices (Singer 1999;Llinas et al 2005).…”
Section: Discussionsupporting
confidence: 49%
“…These reports indicate that low cognitive load is already demanding for patients with schizophrenia. A recent EEG study similarly reported a continuous increase of theta activity with increasing demand on working memory capacities in healthy persons, while theta activity in patients peaked during easy task levels (Missonnier, et al, 2012). The finding that theta amplitudes in patients with schizophrenia are not generally decreased even though the expected increase during perceptual switching is diminished might point towards a similar interpretation (see section 4.1 for further discussion).…”
Section: Overall Disturbances Of Theta Activity In Schizophreniamentioning
confidence: 86%
“…Hong, Moran, Du, O'Donnell, & Summerfelt, 2012;L. E. Hong, Summerfelt, Mitchell, O'Donnell, & Thaker, 2012;Missonnier et al, 2012). Reduced theta activity may be restricted to those recording sites that are involved in task processing in healthy persons, while other recording sites rather show increased activation (BasarEroglu, Schmiedt-Fehr, Marbach, Brand, & Mathes, 2008).…”
Section: Theta Oscillations In Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…This individualrelated electrophysiological parameter may prove to be particularly valuable to evaluate the effect of psychiatric disorders on mental workload. Since mental workload is affected early in some neuropsychiatric disorders like prodromal Alzheimer's disease (Missonnier et al, 2007) and psychotic disorders (Missonnier et al, 2012), early detection of an alteration of our parameter could provide a powerful clinical tool to identify subclinical abnormalities in the early stages of illness and evaluate the performances of psychiatric patients with pre-and post-drug or neuropsychological treatments. As the subject is his own control, this method is particularly well suited to evaluation in the field of ergonomics or cognition in clinical settings.…”
Section: Discussionmentioning
confidence: 99%